Diversity and distribution of Epifaunal and Macroinfaunal Mollusks in Seagrass Beds in Taklong Island, Guimaras - Ermita, Josie Linda A.
Mollusks in seagrass beds are consumed as food, traded for livelihood, or as indicator of environmental quality. This study gives insights on the status of molluscan diversity in seagrass beds within a marine protected area. It generally aims to characterize the molluscan epifaunal and macroinfaunal community structures in selected seagrass beds in Taklong Island National Marine Reserve (TINMR), Guimaras. Three transects per site were established parallel to shore (25 m= inner zone, 35 m= middle zone, 45 m= outer zone). Ten points were chosen per transect, where seagrass blades and sediment core samples were collected for epifauna and macroinfauna analysis, respectively. There was an increasing trend in epifaunal mean density and dominance, while there was decreasing diversity and evenness from inner to outer zones. Gastropods that are adaptive to unstable and more exposed leaf substratum, such as Pyrene sp (D= 5 indiv/1000 cm2) and Cerithium sp (D= 0.6 indiv/1000 cm3) predominate in the epifauna. Meanwhile, there was an increasing trend of macroinfaunal evenness and dominance from inner to outer zone. Bivalves from Family Arcidae (D= ~2 indiv/1000 cm3) and Family Chamidae (D= ~1 indiv/1000 cm3) dominated the macroinfauna which shows that sediments and rhizomes present an ideal environment for sedentary mollusks, like bivalves.